The etiology of delayed sleep phase disorder. (June 2016) - Micic, Gorica; Lovato, Nicole; Gradisar, Michael; Ferguson, Sally A.; Burgess, Helen J.; Lack, Leon C.
Summary: According to classification manuals for sleep disorders, nine disorders are directly related to biological clock timing misalignments. Of all, delayed sleep phase disorder (DSPD) is the most commonly diagnosed, predominantly affecting adolescents, young adults, and insomnia patients. It is a persistent inability to fall asleep at earlier, more desirable and socially conventional times, coupled with extreme difficulty awakening in the morning. Considerable evidence shows a delay in the circadian clock to be associated with DSPD. Therefore, treatments have mainly focused on advancing the biological clock and sleep timing through pharmacotherapy, phototherapy and behavioral therapies. The clinical evidence indicates that these treatments are efficacious, at least in the short term. However, follow up studies show frequent patient relapse, leading researchers to speculate that alternative etiologies may be contributing to sleep and circadian clock delays in DSPD. The aim of the present paper is to review and collate current literature related to DSPD etiology in order to outline gaps in current knowledge and suggest future research.